AN ANALYSIS OF PERSONAL DEIXIS IN SHORT STORY “THE GIFT OF THE MAGI” - Fajar Rahmani, Eka; Meitasari, Putri Eka; Suhartono, Luwandi (LPPM STBA Pontianak, 2023)
The purpose of this study is to characterize and analyze the deicticmanifestations of personal deixis in the short novel Gift of the Magi. This studyspecifically looked at how personal deixis appeared and how context was interpreted.The statements and sentences in the short story served as the main source of the data.The key data used in the research was the percentages of each personal deixis thatappeared in the short narrative, and their interpretation was provided afterward. Theresearchers used a descriptive quantitative design to conduct the study. According tothe research, the short narrative had 231 personal deixes, of which 43 were first-person(18,61%), 14 were second-person (6,06%), and 174 were third-person (75,32%). Inlight of these findings, it was concluded that the Gift of the Magi's author narrated thetale from his point of view to help the readers comprehend the characters, conflicts, andconcepts in the work objectively. Since he is familiar with the entire narrative and thethoughts, emotions, and viewpoints of every character, the author also wishes to projecthis own identity. As a result, the readers are greatly assisted in fully understanding theplot. To put it briefly, to fully appreciate a short story, one must be aware of thefunction of personal deixis.